Preparation method of sodium sulfonate covalent organic framework material and application of sodium sulfonate covalent organic framework material in simultaneous detection and removal of fluoroquinolone antibiotics

CN117164791BActive Publication Date: 2026-10-27HEBEI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311223034.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2026-10-27
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

[0006]为了解决传统COFs的制备对环境污染较大、合成成本较高与反应过程复杂的技术问题,本发明提出了一种磺酸钠共价有机框架材料的制备方法及其同时检测去除氟喹诺酮类抗生素的应用,采用如下技术方案:

Benefits of technology

[0019]本发明的材料制备方法绿色无污染,合成时间短,操作简便;本发明制备的吸附剂材料对FQs具有超大的吸附容量,最大达到1709.6mg·g-1,极大地降低了FQs污染处理成本。同时该材料具有良好的再生性,解决了现有的吸附剂材料难以再生导致的无法推进工业化应用以及环保问题;本发明制备的材料具有稳定的荧光信号,通过FQs对其荧光的猝灭现象,能灵敏地检测FQs的含量,对NOR检测的线性范围为0.03-6μmol·L-1,LOD为8nmol·L-1;本发明制备的材料具有同时检测去除FQs的双重功效,在应用方面更加省时省力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117164791B_ABST
    Figure CN117164791B_ABST
Patent Text Reader

Abstract

The present application relates to the field of adsorption material and fluorescent detection technology, discloses a kind of preparation method of sodium sulfonate covalent organic framework material and its application for simultaneously detecting and removing fluoroquinolone antibiotics, its preparation method includes: step 1, 2, 4, 6-triformylphloroglucinol is ground with 2, 2'-diaminobenzene bisulfonic acid, and an intermediate product is obtained;Step 2, after adding sodium acetate to the intermediate product, the powder is obtained by grinding;Step 3, the powder is sequentially heated, cooled, washed and dried, to obtain covalent organic framework material.The covalent organic framework material prepared by the present application has a simple synthesis process, is easy to operate, and is fast and green and pollution-free in the synthesis process.In terms of its performance, it has good thermal stability and chemical stability, and can selectively adsorb fluoroquinolone antibiotics due to the ionic interface on its surface and the rich negative charge sites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of adsorption materials and fluorescence detection technology, and in particular to a method for preparing a sodium sulfonate covalent organic framework material and its application in the simultaneous detection of fluoroquinolone antibiotics. Background Technology

[0002] With population growth and increasing demand for animal protein, antibiotic consumption is constantly increasing. Fluoroquinolones (FQs) have advantages such as broad-spectrum antibacterial activity, low toxicity, and strong antibacterial effects, and are widely used in medical, livestock, and aquaculture fields. However, only a small amount of FQs can be absorbed and metabolized by humans and animals after administration; most of them enter the environment in the form of active drugs, easily spreading to various water bodies, causing water pollution and posing a great threat to the ecological environment. It has been reported that the concentration of FQs in surface water can reach as high as 2000 ng / L. -1 Enrofloxacin, ciprofloxacin, norfloxacin, and ofloxacin are the most common FQs (free quasi-reactive substances) in water bodies; in the effluent from the United States, the detection rate of norfloxacin and ofloxacin is about 80%, with concentrations of 400-500 ng·L⁻¹. -1 The concentration of ciprofloxacin in the Spanish effluent was approximately 600 ng / L. -1 Therefore, it is necessary to develop an effective and feasible comprehensive material for simultaneously monitoring and removing FQs from water.

[0003] The emergence of various multifunctional adsorbent materials has made integrated detection and removal technology possible. This technology is a novel pollutant treatment technology that partially combines adsorption removal with fluorescence or electrochemical detection at the mechanistic level. Compared to traditional adsorption methods, materials with simultaneous detection capabilities can guide the removal process. Furthermore, compared to single adsorption or detection operations, it simplifies the operation process, reduces costs, and improves pollutant treatment efficiency. These characteristics make integrated detection and removal technology show great potential in the field of water pollutant treatment, and the key to this technology lies in the development and design of multifunctional materials.

[0004] Currently, covalent organic frameworks (COFs) materials possess certain advantages and potential in adsorption and fluorescence detection due to their low density, good stability, high adsorption capacity per unit mass, and long-range conjugated structures. Imine-type COFs, in particular, have attracted widespread attention from researchers in recent years due to their thermal, chemical, and mechanical stability. Methods for synthesizing imine-type COFs mainly include solvothermal methods, microwave methods, liquid-liquid interface polymerization, ultrasonic-mediated polycondensation, and mechanical grinding. Among these methods, mechanical grinding avoids environmental pollution and synthesis costs caused by the use of large amounts of organic solvents, and its simple synthesis conditions and short synthesis time make it the preferred method for green COF synthesis. However, mechanical grinding requires high reactivity of the monomers, resulting in relatively fewer COFs obtained. Traditional COF synthesis requires a certain concentration of acetic acid for catalysis to control the COF formation process. However, the synthesis process with the addition of liquid catalysts is usually complex and time-consuming.

[0005] Therefore, it is essential to establish a solvent-free, green, and rapid synthesis method for COFs with excellent adsorption and fluorescence detection properties. Summary of the Invention

[0006] To address the technical challenges of significant environmental pollution, high synthesis costs, and complex reaction processes in the preparation of traditional COFs, this invention proposes a method for preparing sodium sulfonate covalent organic framework materials and its application in the simultaneous detection of fluoroquinolone antibiotics. The technical solution is as follows:

[0007] On the one hand, the preparation method of sodium sulfonate covalent organic framework materials includes:

[0008] Step 1: Grind 2,4,6-tricarboxymethyl phloroglucinol with 2,2'-benzidine disulfonic acid to obtain an intermediate product;

[0009] Step 2: Add sodium acetate to the intermediate product and then grind it to obtain a powder;

[0010] Step 3: The powder is sequentially heated, cooled, washed and dried to obtain a covalent organic framework material.

[0011] Furthermore, the molar ratio of 2,4,6-tricarboxymethyl phloroglucinol, 2,2'-benzidine disulfonic acid, and sodium acetate is 6:9:100.

[0012] Furthermore, the grinding time in step 1 is 5-10 minutes.

[0013] Furthermore, the grinding time in step 2 is 10-15 minutes.

[0014] Further, the heating in step 3 specifically involves: transferring the powder into a crucible, placing it in an oven for heating at a temperature of 150°C for 1 hour.

[0015] Furthermore, in step 3, the washing is performed by alternating ultrasonic washing with ultrapure water and anhydrous ethanol, followed by centrifugation to obtain the supernatant.

[0016] Furthermore, the drying process described in step 3 specifically involves drying in a vacuum oven for 8 hours at a temperature of 90°C.

[0017] On the other hand, this invention proposes an application of sodium sulfonate covalent organic framework material prepared by the above method in the simultaneous detection and removal of fluoroquinolone antibiotics in the aquatic environment.

[0018] This invention discloses a method for preparing sodium sulfonate covalent organic framework materials and its application in the simultaneous detection of fluoroquinolone antibiotics. Compared with the prior art, its advantages are as follows:

[0019] The material preparation method of this invention is green and pollution-free, with a short synthesis time and simple operation; the adsorbent material prepared by this invention has an extremely large adsorption capacity for FQs, reaching a maximum of 1709.6 mg·g. -1 This significantly reduces the cost of treating FQs pollution. Simultaneously, the material exhibits excellent regenerability, solving the problem of existing adsorbent materials being difficult to regenerate, thus hindering industrial application and environmental protection. The material prepared in this invention possesses a stable fluorescence signal; by observing the quenching of its fluorescence by FQs, the content of FQs can be sensitively detected, with a linear range of 0.03-6 μmol·L⁻¹ for NOR detection. -1 The LOD is 8 nmol·L⁻¹ -1 The material prepared by this invention has the dual function of simultaneously detecting and removing FQs, making it more time-saving and labor-saving in application. Attached Figure Description

[0020] Figure 1 This is a flowchart illustrating the preparation of TpBD-(SO3Na)2 according to an embodiment of the present invention;

[0021] Figure 2 SEM image (ab), TEM image (cd), EDS element distribution (e), and elemental mapping (f) of TpBD-(SO3Na)2;

[0022] Figure 3 XRD pattern (a), FTIR pattern (b), Raman pattern (c), TGA curve (d), N2 adsorption-desorption isotherm (e), and pore size distribution (f) of TpBD-(SO3Na)2;

[0023] Figure 4XPS total spectrum (a) and fine spectrum (bf) of C1s, N1s, O1s, S2p, Na1s for TpBD-(SO3Na)2.

[0024] Figure 5 Comparison of the adsorption capacity of different materials for FQs (a), the effect of adsorbent dosage (b), the effect of pH (c), the effect of ionic strength and HA (d), and the effect of coexisting ions (e);

[0025] Figure 6 For adsorption kinetics fitting (ac), intraparticle diffusion model fitting (df), and adsorption isotherm fitting (gi);

[0026] Figure 7 The adsorption selectivity of TpBD-(SO3Na)2 for FQs was evaluated (a), eluent type optimization (b), eluent volume optimization (c), elution time optimization (d), comparison of regeneration cycles (e), and XRD and FTIR spectra of the material after 8 regenerations compared with those of freshly synthesized TpBD-(SO3Na)2.

[0027] Figure 8 The fluorescence stability of TpBD-(SO3Na)2 over one week (a), the effect of pH on fluorescence detection (b), and the performance of the TpBD-(SO3Na)2 probe at different concentrations (a1: 0, 0.03, 0.06, 0.12, 0.24, 0.48, 1.0, 2.0, 3.0, 4.0, 6.0, 6.0 μmol·L⁻¹) were measured. -1 The fluorescence response of NOR (c), the fluorescence intensity of the TpBD-(SO3Na)2 probe and the NOR concentration in the range of 0-6.0 μmol·L⁻¹ -1 Linearity within the range (d), influence of coexisting ions on fluorescence detection (e);

[0028] Figure 9 The adsorption performance of TpBD-(SO3Na)2 on FQs in actual water samples. Detailed Implementation

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] This invention provides a method for preparing a covalent organic framework material for the simultaneous detection and removal of fluoroquinolone antibiotics (FQs) and its application in the simultaneous detection and removal of FQs in aquatic environments. Addressing the problems of complex preparation methods, high pollution levels, time-consuming processes, and inability to be applied in integrated detection and removal of existing COFs materials, the method for preparing COFs materials in this invention is simple, environmentally friendly, and has a short synthesis time. Furthermore, the COFs materials in this application exhibit ultra-large adsorption capacity and satisfactory detection limits for FQs, effectively solving the problems existing in current materials.

[0031] The method for preparing the covalent organic framework material of the present invention includes the following steps:

[0032] (a) Place the two monomers, 2,4,6-tricarboxymethyl phloroglucinol (Tp) and 2,2'-benzidine disulfonic acid (BD-(SO3H)2), in an agate mortar and grind them until they are uniform and the color does not change.

[0033] (b) Continue to add sodium acetate to the mixture in step (a) and grind until the color does not change and the mixture is in the form of a fine powder;

[0034] (c) The powder obtained in step (b) is transferred to an alumina crucible, heated in an oven, removed, cooled, washed and dried to obtain the product.

[0035] Preferably, in step (a), the molar ratio of Tp and BD-(SO3H)2 monomers is 6:9, and the grinding time is 5-10 minutes.

[0036] Preferably, in step (b), the molar amount of sodium acetate is 100 / 9 times that of BD-(SO3H)2, and the grinding time is 10-15 minutes.

[0037] Preferably, in step (c), the oven temperature is set to 150°C and the heating time is 1 hour. After cooling, the product is ultrasonically washed alternately with ultrapure water and anhydrous ethanol, and the supernatant is separated by centrifugation. The product is then dried in a vacuum oven at 90°C for 8 hours.

[0038] In the above preparation process, solid sodium acetate is added to the grinding system, and the protons on the sulfonic acid groups of the monomer BD-(SO3H)2 react with Na. + Ion exchange occurs. Simultaneously, the generated acetic acid acts as a catalyst for the formation of imine bonds. The slow formation of acetic acid ensures a low acid concentration during COF formation, thereby improving the crystallinity and stability of the COFs.

[0039] The COFs prepared in this invention are named TpBD-(SO3Na)2. This invention provides a comprehensive fitting analysis of the adsorption kinetics, adsorption isotherms, and adsorption thermodynamics of the FQs adsorption process of TpBD-(SO3Na)2. Using the Langmuir adsorption isotherm model, the maximum adsorption capacities of TpBD-(SO3Na)2 for norfloxacin, enoxacin, and ciprofloxacin are 1709.6, 1661.5, and 1362.8 mg·g, respectively. -1 This is the largest among currently reported materials. Adsorption experiments were conducted using the following method: a series of FQs solutions were prepared with ultrapure water containing 10% methanol, with concentrations ranging from 20 to 200 mg / L. -1 Use 0.1 mol·L -1 Adjust the pH of the solution to 7 with HCl or NaOH. The dosage of TpBD-(SO3Na)2 in the FQs solution is 0.05 g·L⁻¹. -1 Different concentrations of FQs solutions with added TpBD-(SO3Na)2 were shaken at 160 rpm for 8 hours. After filtration through a 0.45 μm membrane, the changes in FQs concentration in the solution were measured using a UV-Vis spectrophotometer. The adsorption capacity can be calculated using the following formula:

[0040]

[0041] In the formula, q e (mg·g -1 The expression represents the adsorption capacity of TpBD-(SO3Na)2 for FQs under equilibrium conditions, where C0 and C... e (mg·L -1 ) represents the concentration of FQs at 0 min and at equilibrium, respectively; V (mL) is the volume of the FQs solution; and m (mg) is the dosage of TpBD-(SO3Na)2.

[0042] This invention comprehensively optimized the influencing factors of the adsorption of fluorescein ions (FQs) by TpBD-(SO3Na)2, including the number of sulfonic acid groups and sodium sulfonate on the material surface, the amount of adsorbent added, the pH of the solution, the concentration of salt ions, humic acid (HA), and coexisting ions. It was found that the adsorption performance of different materials for FQs, from highest to lowest, was sodium disulfonate COF > disulfonic acid COF > sodium sulfonate COF > sulfonic acid COF; therefore, TpBD-(SO3Na)2 was selected for subsequent experiments. The optimal adsorbent dosage was 0.05 g·L⁻¹. -1 At pH 7, TpBD-(SO3Na)2 exhibits the highest adsorption capacity for FQs; no salt ions need to be added during the experiment; HA and most coexisting ions have little effect on the adsorption process, only CO32- has a small effect. 2- and HCO3 - Because it will hydrolyze in aqueous solution to form OH -This makes the solution alkaline, which has a certain inhibitory effect on the adsorption process.

[0043] This invention comprehensively studies the adsorption selectivity, regenerability, and stability of the material. By measuring the adsorption capacity of TpBD-(SO3Na)2 for seven major classes of common antibiotics, it was found that TpBD-(SO3Na)2 has a strong affinity for FQs. Using 2.0 mL of 0.1 mol·L⁻¹... -1 Almost all the free radicals (FQs) adsorbed on TpBD-(SO3Na)2 were desorbed by sonication in acetonitrile with HCl for 3 minutes. After 8 adsorption / desorption cycles, the adsorption capacity of TpBD-(SO3Na)2 for FQs remained above 90% of that of the newly synthesized material. XRD and FTIR characterization showed that TpBD-(SO3Na)2 had good regeneration stability. Therefore, TpBD-(SO3Na)2 exhibits high selective adsorption performance for FQs and good reusability. Application in actual water samples further demonstrates the high application value of TpBD-(SO3Na)2 in the selective adsorption of FQs.

[0044] The TpBD-(SO3Na)2 fluorescent probe synthesized in this invention exhibits good fluorescence stability and strong anti-interference ability, enabling quantitative detection of fluorescence ionization (FQs). This probe demonstrates good selectivity and sensitivity. Using NOR as a representative, the solution pH was adjusted to 7, and 1 mg of TpBD-(SO3Na)2 was dispersed in 1 mL of ultrapure water containing 10% methanol. Different concentrations of NOR were added to the dispersion, and the fluorescence intensity was measured after incubation at room temperature for 10 s. Fluorescence intensity was measured at concentrations ranging from 0.03 to 6 μmol·L⁻¹. -1 Within the concentration range, the fluorescence intensity of TpBD-(SO3Na)2 and the concentration fitting curves of NOR showed two good linear relationships, R 2 The values ​​were 0.996 and 0.995, respectively, and the limit of detection (LOD) was 8 nmol·L⁻¹. -1 The application of TpBD-(SO3Na)2 in actual water samples further demonstrates its excellent application value in the field of fluorescence detection of FQs.

[0045] The following will list some embodiments and measurement data of the present invention to illustrate the significant progress of the present invention. It should be noted that reagents or specific operating steps not mentioned in the following embodiments are all conventional techniques in the art and will not be described in detail here.

[0046] reagents

[0047] Tp (97%), BD-(SO3H)2 (70%), NOR, ENO, and CIP were purchased from Aladdin (Shanghai, China). Sodium acetate (>99%) was purchased from Tianjin Damao Chemical Reagent Factory (Tianjin, China). Anhydrous methanol, anhydrous ethanol, hydrochloric acid, and sodium hydroxide were purchased from Tianjin Kemei Chemical Reagent Co., Ltd. (Tianjin, China). Ultrapure water was used in all experiments except for actual sample testing.

[0048] instrument

[0049] F-7000 fluorescence spectrophotometer (Japan); MAPADA-UV6300 double-beam UV-Vis spectrophotometer (China); Tecnai G2 F20 S-TWIN transmission electron microscope (USA); JSM-7500 scanning electron microscope (Japan); PerkinElmer8300 inductively coupled plasma atomic emission spectrometer (USA); Nicolet iS10 Fourier transform infrared spectrometer (USA); Bruker D8 X-ray diffractometer (Germany); Thermo ESCALAB 250Xi X-ray electron spectrometer (USA); Malvern ZS90 Zeta potential analyzer (UK); STA449C differential scanning calorimeter (Germany); Autosorb-iQ-MP surface area analyzer (USA).

[0050] Example 1

[0051] Preparation of COFs

[0052] like Figure 1 As shown, 63 mg Tp and 155 mg BD-(SO3H)2 were placed in an agate mortar and ground continuously with a pestle at room temperature for 5-10 minutes. This resulted in a grayish-white powder that no longer changed color. Next, 684 mg of sodium acetate was added to the mixture, and grinding continued for 10-15 minutes to obtain a bright yellow fine powder that also no longer changed color. The bright yellow powder was then transferred to a corundum crucible and placed in an oven at 150°C for 1 hour. After natural cooling, it was washed alternately with ultrapure water and anhydrous ethanol, and then vacuum dried at 90°C for 12 hours to obtain COFs-TpBD-(SO3Na)2, which has the function of simultaneously detecting the removal of fluoroquinolone antibiotics, for subsequent experiments.

[0053] Example 2

[0054] Material characterization

[0055] The morphology and composition of the synthesized TpBD-(SO3Na)2 were characterized using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), and the results are as follows: Figure 2As shown in the SEM image, TpBD-(SO3Na)2 can be clearly seen to consist of irregular blocky aggregates with a size of approximately 200 nm (see...). Figure 2 (a) and Figure 2 (b)). In the TEM image, the crystal lattice of TpBD-(SO3Na)2 can be clearly observed under high magnification, indicating that the synthesized material has a certain crystal form (see...). Figure 2 (c) and Figure 2 (d)). SEM-EDS elemental distribution confirmed the presence of five elements—C, N, O, S, and Na—in the synthesized TpBD-(SO3Na)2, and SEM-Mapping also confirmed that these elements are uniformly distributed on the material surface (see [link]). Figure 2 (e) and Figure 2 (f) The contents of Na and S in the synthesized TpBD-(SO3Na)2 were quantitatively determined by inductively coupled plasma atomic emission spectrometry. The results showed that the contents of Na and S were 8 wt% and 11 wt%, respectively, which were not significantly different from the theoretical values ​​of 9.3 wt% and 13 wt%. These test results indicate that effective elemental substitution occurred during the synthesis of TpBD-(SO3Na)2.

[0056] The crystal structure of TpBD-(SO3Na)2 was characterized by X-ray diffraction. Figure 3 As shown in section (a), the diffraction peak at 4.6° belongs to the {100} plane of the hexagonal orientation of the ordered lattice arrangement, and the diffraction peak near 20° confirms the π-π stacking of TpBD-(SO3Na)2. To further determine the crystal structure of the synthesized TpBD-(SO3Na)2, structural models with different stacking modes were simulated using MaterialsStudio software, and it was found that the synthesized material conforms to the AA oblique stacking mode.

[0057] Fourier transform infrared spectroscopy (FT-IR) further confirmed the successful synthesis of TpBD-(SO3Na)2. Figure 3 As shown in section (b), in the spectrum of the synthesized TpBD-(SO3Na)2, the Tp monomer is at 2900 cm⁻¹. -1 CH and 1645cm -1 The characteristic peak of C=O at this location disappears, and the NH content in BD-(SO3H)2 (3200-3400 cm⁻¹) decreases. -1 The tensile vibration signal also disappeared, indicating that a Schiff base reaction occurred between Tp and BD-(SO3H)2. Simultaneously, C=C (1562cm³) appeared in TpBD-(SO3Na)2. -1 ) and CN (1232cm -1The characteristic peaks of the stretching vibrations indicate that partial enol-ketone tautomerism occurred during the formation of TpBD-(SO3Na)2. Additionally, at 1047 cm⁻¹... -1 and 1030cm -1 The newly appearing characteristic peaks nearby belong to -SO3 - Loci at 1200, 701, 624, and 543 cm -1 The characteristic peak appearing at O=S=O can be attributed to the symmetric and asymmetric stretching bands. For example... Figure 3 As shown in section (c), at 1059cm -1 and 1600cm -1 The Raman characteristic peak at 1408 cm⁻¹ is caused by the stretching vibrations of the benzene ring and C=C bonds. -1 The peak at that point belongs to the CN bond stretching vibration, indicating that the aldehyde ligand and the amino ligand underwent Schiff base condensation, which is consistent with the FT-IR characterization.

[0058] The synthesis of TpBD-(SO3Na)2 under nitrogen atmosphere was analyzed at a heating rate of 10 °C·min. -1 Thermal stability. For example... Figure 3 As shown in section (d), the thermal degradation of TpBD-(SO3Na)2 proceeds primarily in two steps. The first step involves a 6% weight loss before 100℃, due to the volatilization of adsorbed water and other solvents in the sample. The second thermal degradation occurs at 483℃, corresponding to the collapse of the COF framework and structural decomposition. Even when the temperature is further increased to 800℃, TpBD-(SO3Na)2 still retains 60% of its initial weight, indicating good thermal stability, which is beneficial for the material's application at high temperatures.

[0059] The nitrogen adsorption-desorption isotherm of TpBD-(SO3Na)2 was measured at 77 K, and the results are as follows: Figure 3 Middle (e) part and Figure 3 As shown in section (f), the adsorption isotherm of TpBD-(SO3Na)2 belongs to type IV, indicating the presence of a mesoporous structure within the material. Pore size distribution calculations show that the main pore size is 3.8 nm, with a weak peak at 6.7 nm, which may be due to voids generated during COF aggregation. The specific surface area of ​​TpBD-(SO3Na)2 is 37.44 m². 2 ·g -1 This may be due to its low crystallinity and the large number of sulfonic acid groups occupying the pores.

[0060] X-ray photoelectron spectroscopy (XPS) analysis was performed on the synthesized TpBD-(SO3Na)2, and the results are as follows: Figure 4 As shown. From Figure 4The overall spectrum in section (a) clearly shows that the material is composed of carbon, oxygen, nitrogen, sulfur, and sodium, confirming the successful preparation of sodium sulfonate COF. The C1s spectrum can be divided into four peaks with binding energies of 284.8, 285.9, 287.7, and 290.1 ​​eV, corresponding to C–C / C=C, C–N / C=N, C–O / C=O, and π-π* bonds, respectively (see...). Figure 4 (b)). In the N1s spectrum, the two peaks at 40.1 eV and 403.8 eV are attributed to the NH / CN bond and the imine-N bond (see [link to N1s spectrum]). Figure 4 (c)). The O1s spectrum was split into three peaks with binding energies of 531.9, 533.7, and 536.2 eV, corresponding to the CO / C=O bond, S=O / SO bond, and hydroxyl group, respectively (see [link to O1s spectrum]). Figure 4 (d)). The high-resolution XPS spectrum of S2p is divided into three peaks at 168.1, 168.5, and 169.3 eV, corresponding to -SO3, respectively. - S-Na and CS (see Figure 4 (e)). These results further confirm the formation of the TpBD-(SO3Na)2 structure.

[0061] Example 3

[0062] Adsorption conditions optimization

[0063] To verify the effect of the number of sulfonic acid groups or sodium sulfonate on the surface of COFs on the adsorption performance of FQs, the adsorption capacities of TpPa-SO3H, TpPa-(SO3H)2, TpBD-SO3Na, and TpBD-(SO3Na)2 for three FQs (NOR, ENO, and CIP) were measured. Figure 5 As shown in section (a), the adsorption capacity of COF synthesized from disulfonic acid monomers is significantly improved compared to COF synthesized from a single sulfonic acid monomer. Further replacing the protons on the sulfonic acid groups of the COF with sodium ions can further enhance its adsorption capacity. Moreover, when sodium ions replace the protons on the disulfonic acid COF, the adsorption capacity of the material for FQs can be increased by more than 10 times. Therefore, increasing the number of sulfonic acid groups and substituting with sodium ions can effectively improve the adsorption capacity of COFs for FQs. This phenomenon is mainly due to the fact that changes in the pore structure of the COF and the increase in pore size and adsorption sites can effectively promote the adsorption of FQs.

[0064] To achieve the best adsorption effect, the present invention optimized the adsorbent dosage and solution pH, such as... Figure 5 As shown in section (b), the adsorption temperature was fixed at 30℃, the adsorption time was 420 minutes, and the initial concentration of FQs was 20 mg·L⁻¹. -1 As the amount of adsorbent increased from 0.0025 g·L⁻¹ -1Gradually increase to 0.05 g·L -1 The adsorption capacity of TpBD-(SO3Na)2 for FQs increases rapidly. However, with further increases in adsorbent dosage, the adsorption capacity of TpBD-(SO3Na)2 for FQs decreases significantly. Therefore, this invention selects 0.05 g·L⁻¹. -1 The amount of adsorbent added will be used in the following experiments.

[0065] The effect of TpBD-(SO3Na)2 on the adsorption capacity of FQs at different pH values ​​is as follows: Figure 5 As shown in section (c), the adsorption capacity of TpBD-(SO3Na)2 for FQs gradually increases from pH 3 to 7, reaching its maximum at pH 7. As the alkalinity of the solution increases, the adsorption capacity of TpBD-(SO3Na)2 for FQs decreases rapidly. Therefore, this invention selected pH = 7 for the subsequent experiments.

[0066] Furthermore, the effects of different concentrations of NaCl, HA, and different coexisting ions on the adsorption process of FQs were investigated. Under the same conditions, 0-600 mg·L⁻¹ of NaCl, HA, and different coexisting ions were added to the FQs solution. -1 The effect of salinity on the adsorption capacity of NaCl was investigated.

[0067] like Figure 5 As shown in Figure (d), when the NaCl concentration is between 0-50 mg·L⁻¹ -1 As the salinity of the solution increased, the adsorption capacity of TpBD-(SO3Na)2 for FQs remained almost unchanged. With further increases in solution salinity, the adsorption capacity of FQs decreased significantly due to the charge shielding effect. In aqueous solutions with high ionic strength, the contribution of electrostatic interactions to adsorption was completely suppressed. When the NaCl concentration reached 30 times the FQs concentration, the adsorption capacity decreased by about half. This is likely because the large amount of inorganic salt increased the solution viscosity, leading to increased diffusion resistance of FQs to the adsorbent. Furthermore, free NaCl around TpBD-(SO3Na)2 occupied adsorption sites on the surface, neutralizing the surface charge and hindering the electrostatic interaction between the adsorbent and FQs molecules. Therefore, to ensure maximum adsorption capacity of FQs, no salt was added in subsequent experiments. HA is a typical organic compound widely found in natural water bodies, containing various functional groups such as carboxyl, hydroxyl, carbonyl, thiol, aromatic rings, lipid rings, and benzene rings. Adding 0-80 mg·L⁻¹ to the FQs solution... -1 The HA (hygroscopic adsorption) is used to study the effect of organic matter on the adsorption capacity of materials. For example... Figure 5 As shown in section (d), when the HA concentration increases from 0 mg·L⁻¹... -1 Increase to 80 mg·L -1At that time, the adsorption capacity of TpBD-(SO3Na)2 for FQs decreased by about 10%. The functional groups on HA bind to TpBD-(SO3Na)2 through hydrogen bonds, electrostatic interactions, and π-π interactions, causing HA to compete with FQs for active adsorption sites on the adsorbent. However, the affinity of TpBD-(SO3Na)2 for FQs is much higher than that of HA, so the effect of HA can be ignored in practical applications.

[0068] To verify the effect of coexisting anions and cations, monovalent ions (Na+, Na ... + K + Cl - ,Br - F - I - Ac - NO 3- HCO 3- ), divalent ions (Ca) 2+ Mg 2+ Pb 2+ Zn 2+ Cu 2+ Fe 2+ CO3 2- SO3 2- SO4 2- ) and trivalent ions (Al) 3+ Fe 3+ Adsorption experiments were conducted. For example... Figure 5 As shown in section (e), except for Fe 2+ Aside from the potential shielding effect, the presence of most cations does not have a significant negative impact on the adsorption of FQs. Among anions, due to CO32-... 2- and HCO 3- In aqueous solution, it will undergo hydrolysis to form OH-. - The alkalinity of the solution significantly inhibits the adsorption process. Although a few cations and anions have some negative impact on the adsorption process of FQs, the adsorption capacity of TpBD-(SO3Na)2 for FQs remains at a high level.

[0069] Example 4

[0070] Adsorption kinetics fitting

[0071] like Figure 6 As shown in sections (a)-(c), pseudo-first-order and pseudo-second-order kinetic models were used to fit the changes in adsorption capacity over time, and the adsorption kinetics at different FQs concentrations were also compared laterally. Table 1 shows the Ri of the pseudo-second-order adsorption kinetic model. 2Since both values ​​are greater than 0.98, the pseudo-second-order adsorption kinetic model is more suitable for describing the adsorption process of FQs on TpBD-(SO3Na)2. This indicates that chemisorption controls the adsorption rate of FQs molecules on TpBD-(SO3Na)2.

[0072] like Figure 6 As shown in sections (d)-(f), an intraparticle diffusion model was used to fit the experimental data to investigate the limiting factors of the diffusion rate of chemisorption ions (FQs) on the TpBD-(SO3Na)2 surface. The adsorption process of FQs can be divided into three stages. The first stage is the liquid film diffusion stage, where FQs molecules diffuse from the solution to the boundary layer of TpBD-(SO3Na)2, resulting in a sharp increase in adsorption. In the second stage, FQs further diffuse into the pores of TpBD-(SO3Na)2 and bind to the active sites on the adsorbent surface. The adsorption rate in this stage is significantly slower than in the first stage, and the slope is also gentler. The correlation coefficients in the second stage are all lower than those in the first stage, indicating that chemisorption mainly occurs in the second stage. In the third stage, the adsorption sites are basically occupied, the concentration of FQs in the solution is low, and the adsorption gradually reaches equilibrium. For the adsorption process, none of the three linear segments of the model pass through the origin, indicating that intraparticle diffusion is not the only rate-controlling step. Therefore, it is considered that the adsorption rate of FQs is jointly determined by surface adsorption, film diffusion, and intraparticle diffusion.

[0073] Table 1. Adsorption kinetic fitting parameters (303K)

[0074]

[0075]

[0076] Example 5

[0077] Adsorption isotherms and adsorption thermodynamic fitting

[0078] like Figure 6 As shown in (g)-(i), an initial concentration of 20-200 mg·L⁻¹ was established. -1 Adsorption isotherms of FQs in the 30-50 °C range were obtained using Langmuir, Freundlich, Temkin, and Sips models. The results showed that the Langmuir model was best suited to describe the adsorption process of FQs by TpBD-(SO3Na)2 (see Table 2); the maximum adsorption capacities for NOR, ENO, and CIP were 1709.6, 1661.5, and 1362.8 mg·g⁻¹, respectively. -1 This is the largest among currently reported materials, as shown in Table 3. Furthermore, the fitting error χ² of the model is... 2Observations revealed that the Sips model had the smallest errors for NOR, ENO, and CIP, at 1.43, 0.59, and 0.93 respectively, indicating that the Sips model appropriately describes the adsorption process of TpBD-(SO3Na)2 on FQs. The Sips model is a combination of the Langmuir and Freundlich models; therefore, the adsorption process mainly occurs as monolayer adsorption, with uneven distribution of active sites and multilayer adsorption phenomena also present. Furthermore, the correlation coefficient of the Temkin model is greater than 0.98, indicating that the adsorption process is mainly chemisorption.

[0079] like Figure 6 As shown in sections (g)-(i), the adsorption capacity of FQs by TpBD-(SO3Na)2 gradually increases with increasing temperature, indicating that appropriately increasing the temperature can improve the adsorption performance of the material for FQs. This adsorption process is endothermic. A moderately increased temperature may cause some expansion of the internal structure of the adsorbent, making it easier for adsorbate molecules to penetrate into its pores. Furthermore, as the temperature increases, the diffusion rate of FQs through the outer boundary layer into the internal pores of the adsorbent accelerates, resulting in a larger adsorption capacity. The temperature dependence of the adsorption process was obtained by calculating thermodynamic parameters such as Gibbs free energy (ΔG), standard enthalpy change (ΔH), and standard entropy change (ΔS). As shown in Table 4, ΔG is negative, indicating that the adsorption of FQs by TpBD-(SO3Na)2 is spontaneous and feasible. ΔG decreases with increasing temperature, indicating that the adsorption of FQs is more spontaneous and favorable at higher temperatures, confirming the results of the temperature effect discussion. (The last sentence appears to be incomplete and requires further context.) d The positive value of ΔH calculated from the relationship with 1 / T confirms that the adsorption process is endothermic, reflecting that increased temperature increases the affinity of TpBD-(SO3Na)2 for FQs. The positive value of ΔS indicates an increase in the randomness of the solid-liquid interface during adsorption.

[0080] Table 2. Fitting parameters for adsorption isotherms (taking NOR as an example)

[0081]

[0082]

[0083] Table 3. Comparison of adsorption performance of TpBD-(SO3Na)2 and previously reported adsorbents for FQs

[0084]

[0085]

[0086] Table 4 Adsorption thermodynamic fitting parameters

[0087]

[0088] Example 6

[0089] Adsorption selectivity, recyclability and stability

[0090] The adsorption selectivity of TpBD-(SO3Na)2 for seven major classes of common antibiotics was evaluated by measuring their adsorption capacity. Figure 7 As shown in section (a), TpBD-(SO3Na)2 exhibits the highest adsorption capacity for FQs class antibiotics, while its adsorption capacity for other classes of antibiotics is very low, indicating that TpBD-(SO3Na)2 has a strong affinity for FQs.

[0091] After the adsorption experiment, a suitable elution solvent was selected to elute the FQs in the adsorbent, and the regeneration performance of the material was evaluated. The regeneration performance was tested with methanol, acetonitrile, acetonitrile containing 10% methanol, acetonitrile containing 5% ammonia, and 1 mol·L⁻¹ solvent. -1 Acetic acid, 0.1 mol·L -1 Hydrochloric acid, containing 0.05 mol·L -1 Acetonitrile of hydrochloric acid, containing 0.1 mol·L -1 Eight elution solvents, including hydrochloric acid and acetonitrile. Figure 7 As shown in section (b), it contains 0.1 mol·L⁻¹ -1 HCl has the best desorption effect on acetonitrile, and can desorb almost all FQs.

[0092] The effect of the amount of elution solvent was also investigated. When the concentration was 0.1 mol·L⁻¹ -1 When the volume of acetonitrile in HCl increased from 0.5 to 2.0 mL, the desorption of FQs gradually increased, but the elution efficiency did not change significantly with further increases in the volume of the eluent (see...). Figure 7 (c) Therefore, a desorption volume of 2.0 mL was chosen. The ultrasonic desorption time was also optimized. As the ultrasonic time increased from 1 min to 3 min, the desorption effect gradually increased, and with further increases in ultrasonic time, the desorption effect did not change significantly. Figure 7 (d) Therefore, the optimal desorption time is 3 min. After the above optimized desorption steps, the material is washed with ultrapure water, dried under vacuum at 30°C, and then proceeded to the next adsorption experiment. Figure 7 Part (e) summarizes the changes in adsorption capacity during eight adsorption / desorption cycles. It was found that after eight cycles, the adsorption capacity of TpBD-(SO3Na)2 for FQs remained above 90% of the adsorption capacity of the newly synthesized material, indicating that the adsorption performance of the regenerated TpBD-(SO3Na)2 was relatively stable. Figure 7As shown in sections (f) and (g), the regeneration stability of TpBD-(SO3Na)2 was further verified by XRD and FTIR characterization. Therefore, TpBD-(SO3Na)2 exhibits high selective adsorption performance for FQs and good reusability, making it highly valuable for the selective adsorption of FQs.

[0093] Example 7

[0094] Fluorescence detection FQs

[0095] The optimal excitation wavelength for TpBD-(SO3Na)2 is 368 nm, with the strongest emission peak at 520 nm, emitting bright orange fluorescence under ultraviolet light. Figure 8 As shown in section (a), the fluorescence intensity of TpBD-(SO3Na)2 did not show significant decay over 7 days, demonstrating that TpBD-(SO3Na)2 has excellent fluorescence stability.

[0096] The detection pH was optimized by measuring the fluorescence intensity of TpBD-(SO3Na)2 under different pH conditions and the change in fluorescence intensity upon the addition of NOR. Figure 8 As shown in section (b), the fluorescence intensity of TpBD-(SO3Na)2 changed significantly within the pH range of 3-11, and the degree of fluorescence quenching of TpBD-(SO3Na)2 by the same concentration of NOR also varied. Considering the optimal adsorption pH conditions, pH=7 was selected as the optimal detection pH, which is consistent with the optimal pH value for the adsorption process.

[0097] To comprehensively evaluate the detection capability of TpBD-(SO3Na)2 for fluorescence quenching (FQs), NOR was selected as the research subject. Under optimal conditions, a series of fluorescence experiments were conducted to explore the relationship between NOR concentration and TpBD-(SO3Na)2 fluorescence quenching. Figure 8 As shown in section (c), the fluorescence intensity of TpBD-(SO3Na)2 decreased significantly with increasing NOR concentration. Fluorescence quenching was clearly observed under UV light. The results indicate that within the NOR concentration range of 0.03–6 μmol·L⁻¹, the fluorescence intensity of TpBD-(SO3Na)₂ decreased significantly. -1 Within the range, the fitted curves exhibit two good linear relationships, R0 2 They are 0.996 and 0.995 respectively. Figure 8 (d) The LOD calculated using a three-fold signal-to-noise ratio / slope is 8 nmol·L⁻¹. -1The above results demonstrate that the prepared TpBD-(SO3Na)2 exhibits high detection sensitivity, a wide linear range, and low LOD for NOR. TpBD-(SO3Na)2 shows good application potential in FQs fluorescence detection. As shown in Table 5, the performance of different materials in FQs fluorescence detection was compared, and TpBD-(SO3Na)2 showed certain advantages. To further verify the anti-interference ability of TpBD-(SO3Na)2 in FQs fluorescence detection, potentially coexisting ions were added to the detection system. Figure 8 As shown in section (e), the fluorescence quenching effect of NOR on TpBD-(SO3Na)2 is unaffected in the presence of most cations and anions at the same concentrations. Although Fe 2+ and Fe 3+ The fluorescence intensity of TpBD-(SO3Na)2 is quenched to some extent, but the effect is negligible compared to the quenching rate of NOR on the material. The results indicate that TpBD-(SO3Na)2 exhibits good selectivity and anti-interference properties for FQs detection. The fluorescence quenching mechanism is speculated to be competitive energy adsorption or photoinduced electron transfer between the two components on their surfaces.

[0098] Table 5. Comparison of FQs detection capabilities between TpBD-(SO3Na)2 and previously reported fluorescent probes.

[0099]

[0100]

[0101] Example 8

[0102] Application in actual water samples

[0103] To investigate the adsorption effect of TpBD-(SO3Na)2 on FQs in a real aquatic environment, five representative water samples were selected, including tap water and four samples from Baiyangdian Lake. Figure 9As shown, although the adsorption capacity of TpBD-(SO3Na)2 for FQs in actual water samples decreased slightly compared with the adsorption effect in ultrapure water, it still exhibited high adsorption performance. The slight decrease in adsorption capacity may be due to interference from inorganic and organic substances in the relatively complex actual water samples. Furthermore, to verify the ability of TpBD-(SO3Na)2 to detect FQs fluorescence in actual water samples, a spiked recovery experiment was conducted. Fluorescence detection was performed on pretreated water samples and pretreated water samples with different concentrations of standard NOR. As shown in Table 6, NOR was not detected in tap water and four Baiyangdian water samples, with spiked recoveries ranging from 86.0% to 114.0%. These results indicate that TpBD-(SO3Na)2 has certain application prospects in the integrated detection and removal of FQs in actual water samples.

[0104] Table 6. Results of NOR detection in actual water samples using TpBD-(SO3Na)2.

[0105]

[0106]

[0107] Note: "ND" indicates not detected.

[0108] In summary, this invention synthesizes a COF with dual functions of selective detection and adsorption of fluorescein ions (FQs) in aquatic environments using a green, solvent-free mechanical grinding method. The adsorption selectivity mainly originates from electrostatic and hydrogen bonding interactions, while the fluorescence detection mechanism likely involves a combination of internal filtration and photoinduced electron transfer. Furthermore, the material exhibits good reusability and anti-interference capabilities, demonstrating promising application prospects in real-world water samples. Additionally, this invention provides a practical and theoretical foundation for the rapid synthesis of novel green adsorbents and their efficient adsorption and detection of FQs in aquatic environments.

[0109] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. The application of a sodium disulfonate-functionalized covalent organic framework material in the simultaneous detection and removal of fluoroquinolone antibiotics in an aqueous environment, characterized in that, Includes the following steps: Step 1: Grind 2,4,6-tricarboxymethyl phloroglucinol with 2,2'-benzidine disulfonic acid to obtain an intermediate product; Step 2: According to the molar ratio of 2,4,6-tricarboxymethyl phloroglucinol, 2,2'-benzidine disulfonic acid and sodium acetate, solid sodium acetate was added to the intermediate product and then ground to obtain a powder. In the grinding system, the proton on the sulfonic acid group of monomer BD-(SO3H)2 undergoes ion exchange with Na, and the generated acetic acid acts as a catalyst to catalyze the formation of imine bonds. Step 3: The powder is sequentially heated, cooled, washed and dried to obtain a covalent organic framework material. Specifically, the heating involves transferring the powder to a crucible and placing it in an oven for heating at 150°C for 1 hour.

2. The application of a sodium disulfonate functionalized covalent organic framework material according to claim 1 in the simultaneous detection and removal of fluoroquinolone antibiotics in an aqueous environment, characterized in that, The grinding time in step 1 is 5-10 minutes.

3. The application of a sodium disulfonate functionalized covalent organic framework material according to claim 1 in the simultaneous detection and removal of fluoroquinolone antibiotics in an aqueous environment, characterized in that... The grinding time in step 2 is 10-15 minutes.

4. The application of a sodium disulfonate functionalized covalent organic framework material according to claim 1 in the simultaneous detection and removal of fluoroquinolone antibiotics in an aqueous environment, characterized in that, In step 3, the washing process involves alternating ultrasonic washing with ultrapure water and anhydrous ethanol, followed by centrifugation to obtain the supernatant.

5. The application of a sodium disulfonate functionalized covalent organic framework material according to claim 1 in the simultaneous detection and removal of fluoroquinolone antibiotics in an aqueous environment, characterized in that, The drying process described in step 3 specifically involves drying in a vacuum oven for 8 hours at a temperature of 90°C.